The dynamics of Chironomidae (Insecta : Diptera) assemblages in response to environmental change during the past 700 years on Svalbard - Brooks, SJ; Birks, HJB (KLUWER ACADEMIC PUBL, 2004)
The impact of recent natural and human-induced environmental change on chironomid faunas on Svalbard has been investigated. The modern chironomid fauna was studied from surface-sediment samples collected from 23 lakes in western Svalbard. A total of 18 taxa was found, of which three had not been recorded previously from Svalbard. The influence of water chemistry and physical variables on the distribution and abundance of the modern chironomid assemblages was investigated using correspondence analysis and multiple regression. The chironomid assemblages fall into four groups, which are primarily influenced by pH, nutrient concentrations, water temperature, and water depth. Sediment cores were taken from three lakes to investigate changes in chironomid assemblages over the last 700 years. At two of the sites there is evidence for a response to regional climatic change occurring about 200 years ago and may have been associated with the 'Little Ice Age'. At the third site there is a response to local catchment changes, probably brought about, initially, by the establishment of a human settlement close to the lake 70 years ago, and subsequently, as a result of the abandonment of this settlement in 1988.